Comparison of semi- spherical solar collector with flat plate solar collector - moravej, mojtaba; Namdarnia, Fatemeh; Esmaili, Leila (International Journal of Engineering and Technology, 2019)
The efficiency of each solar system depends on the amount of radiation that it receives. The evident characteristic of solar energy is its change throughout the day and during different seasons. Another feature of this energy is the change of position of the sun in the sky relative to Earth. The greatest amount of radiation from the sun comes when the sun's rays rise vertically to the desired level. For this reason, in solar collector systems, the collector must rotate to the sun, otherwise, the amount of accumulated energy falls. The purpose of this paper is to compare the performance of a solar semi- spherical collector with a flat plate collector. In this study, the semi- spherical solar collector does not need to be placed in a specific direction and also does not need the sunlight tracking mechanism to get the most amount of sunlight. Due to the semi- spherical shape of this collector, all geographic directions have the same effect. It also exhibits the highest resistance to wind blowing in terms of greater stability and lack of vibration and destruction. But the flat plate collector should be in the direction of radiation. In this research, experimental data from a flat plate collector in a closed cycle have been investigated with experimental data from a semi- spherical solar collector, simultaneously and it is shown that reducing the radiation or wind velocity will have the greatest impact on the flat plate collector and its outlet temperature. The experiments showed that the highest efficiency was in semi-spherical solar collector and it was about 67% and the highest outlet water temperature was in the flat collector and around 76Â°C.Â Â Â Â